Swank report its implementation in the U.P. Library administration - Lee, Kyunghui (1970)
This study evaluated improvements implemented based on Dr. Swank's study in 1954 of the libraries of the University of the Philippines. Findings showed that improvements in the library services from 1960 to 1969 have been guided by the Swank Report. Many of his recommendations have been implemented in full while some were implemented with some modifications based on actual needs. A few recommendations have not been workable. In general though, the period of 15 years, from 1954 to 1969, has proven that Dr. Swank's recommendations have been very helpful in achieving sound library management.